"Wir haben getan, was wir zu tun schuldig waren" (Lukas 17, 10). Festschrift zur Ehrenpromotion von Helmut Greve - Gutmann, Hans-Martin (Hamburg University Press, 2008)
This volume documents the speeches that were given during the academic celebration on the occasion of the award of the dignity of Dr. theol. honoris causa to Prof. Dr. Helmut Greve at the University of Hamburg on November 19, 2007.